Qualitative Descriptive Study of Virtual Personal Branding on Tiktok Social Media Account @Vmuliana - Ali, M Farrel Maolana; Santoso, Didik Haryadi; Nuryana, Arief (Formosa Journal of Computer and Information Science, 2025)
Tiktok is a social media platform that uses video features that can use background sound with a duration of approximately 15 seconds -3 minutes. Tiktok has another function, namely being able to build a virtual personal brand. A content creator and employee of the State-Owned Enterprises Agency (BUMN), namely Vina Muliana, is quite famous among the Indonesian people in distributing content packaged in a unique and fun way on the Tiktok account @vmuliana. This study aims to find out how Vina Muliana's Virtual Personal Branding is on her TikTok. Problems with the study The focus is on virtual personal branding and in her research, the theory of the four concepts of Authentic Building Success Personal Branding by Hubert K. Rampersad is used as a reference. Data was collected through interviews and video documentation uploaded to the Tiktok account @vmuliana using a qualitative approach. This study concludes that the virtual personal branding carried out by Vina Muliana @vmuliana fulfills the four concepts of personal branding that have been elaborated using virtual reality references, namely Virtual Authenticity, Virtual Consistency, Virtual Specialization, and Virtual Persistence